PENGARUH LEVERAGE, PROFITABILITY, DAN FIRM SIZE TERHADAP CASH HOLDING - Hadryan, Matthew; Susanti, Merry (Fakultas Ekonomi, Universitas Tarumanagara, 2024)
This study was conducted to determine the results of the effect of leverage, profitability, and firm size on cash holding. In this study, using manufacturing companies listed on the Indonesia Stock Exchange as research subjects. The technique used to collect the sample is purposive sampling technique. There were 64 companies that were selected as samples and used the Eviews (Economic Views) version 12 program to process the data. In the test conducted, the researchers found that leverage had a negative and significant effect on cash holding, profitability had a positive and significant effect on cash holding, and firm size had a positive and insignificant effect on cash holding.